Predictive Role of NEK6 in Prognosis and Immune Infiltration in Head and Neck Squamous Cell Carcinoma - Yang, Zhi-Min; Liao, Bing; Yang, Si-Si; Su, Tong; Zhang, Jing; Wang, Wei-Ming (Frontiers in Endocrinology, 2022)
Head and neck squamous cell carcinoma (HNSC), as one of the common malignant tumors, seriously threatens human health. NEK6 (Never in Mitosis A (NIMA) related kinases 6), as a cyclin, promotes cancer cell proliferation and cancer progression. However, the prognostic value of NEK6 and its correlation with immune cell infiltration in HNSC remain unclear. In this study, we comprehensively elucidated the prognostic role and potential function of NEK6 expression in HNSC. The expression of NEK6 was significantly up-regulated by immunohistochemistry in HNSC. Upregulation of NEK6 expression in gene expression studies predicts poor prognosis in HNSC patients. The results of Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene set variation analysis indicated that NEK6 is mainly involved in extracellular matrix metabolism and EMT processes. The expression of NEK6 increased with the level of immune cell infiltration and the expression of various immune checkpoints. In conclusion, NEK6 may serve as a candidate prognostic predictor and may predict the response of HNSC patients to immunotherapy.